BEYOND BALANCED SCORECARD: KINERJA ORGANISASI BERNUANSA RELIGIUSITAS - Hanif Hanif (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
This study aims to explore the meaning of comprehensive performance measurement from the perspective of the individual manager of the Health Service Organization X in Jakarta. The research method uses transcendental phenomenology. Researchers visited to the field, to understand the research site, discuss, and conduct interviews. The results of the discussions and interviews were analyzed according to transcendental phenomenology research procedures, namely noema, finding the most surface meaning, then noesis, the deeper meaning part, then doing ephoce (bracketing), intentional analysis, and eidetic reduction to arrive at the discovery of